The role of comparing in financial markets with hidden information - Juha-Pekka Niinimäki; Tuomas Takalo; Klaus Kultti (Bank of Finland, 2006)
This paper studies how comparing can be used to provide information in financial markets in the presence of a hidden characteristics problem.Although an investor cannot precisely estimate the future returns of an entrepreneur's projects, the investor can mitigate the asymmetric information problem by ranking different entrepreneurs and financing only the very best ones.Information asymmetry can be eliminated with certainty if the number of compared projects is sufficiently large.Because comparing favours centralised information gathering, it creates a novel rationale for the establishment of a financial intermediary.
URN:NBN:fi:bof-20140807578
Keywords: G21; G24; 330; asymmetric information; banking; corporate finance; financial intermediation; ranking; venture capital